Intensity of Watching Violent Shows on Television and Tendency to Aggressiveness in Adolescents (Study of Class IX Students of MTS Negeri 1 Bangil) - Iqbal Fikri (Psikologia : Jurnal Psikologi, 2013)
Many violence cases as brawls and fights whose committed by juveniles were caused by many factors. This study aimed to find out the relationship between the intensity of watching violence on television with aggressiveness tendencies in adolescents. This study used a quantitative correlation approach that using the intensity watching violence on television as an independent variable (X) and the tendency of aggressiveness as the dependent variable (Y). The sampling technique used random sampling to 69 students of class IX in MTs Negeri 1 Bangil. Measurement of variables used both of two psychologycal scales that constructed by researchers, namely the intensity of watching violence on television scale and aggressiveness tendency scale. Correlation technique of product moment from Pearson was used to analyze data which of calculation helped by SPSS 16.0 for Windows. The result showed that (r) = 0.404; ρ = 0.001 < ρ = 0.01. It means, there is a significant relationship and positive, the higher of the intensity of watching violence on television, the higher of the aggressiveness tendencies in adolescents and vice versa.